Advance technique to predict eating quality of ripe-mango at unripe-stage using near infrared spectroscopy - S. Saranwong (2018)
A technique to predict eating quality, Brix value, of ripe mango from its harvest quality, measured nondestructively by near infrared (NIR) spectroscopy, was successfully developed. The NIR spectra in the short wavelength region (700 to 1100 nm) of unripe mangoes were measured immediately after harvest. Calibration equations for harvest indices, dry matter (DM) and starch content, were developed (SEP: 0.41% w/w for DM, 1.71% w/w for starch). From the NIR spectra measured and the calibration equation developed, the relationship between harvest quality and Brix value at the ripe stage of the same mangoes was revealed. Ripe mangoes would have high Brix value if the fruit contained sufficient amounts of DM and starch at harvest date. Brix value of ripe mangoes could be precisely predicted from the DM and starch measured nondestructively with NIR at harvest. The standard error of prediction (SEP) for the Brix calibration equation was 0.55 °Brix.